2022
DOI: 10.1503/cjs.013120
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gender-based and sexual harassment within orthopedic surgery in Canada

Abstract: Background: Gender-based and sexual harassment are prevalent in the medical profession. We aimed to quantify the prevalence of such behaviours within orthopedic surgery in Canada and to identify any risk factors for experiencing gender-based or sexual harassment in the workplace. Methods:In collaboration with the Canadian Orthopaedic Association, we conducted a Canada-wide email questionnaire survey in June 2019 of all orthopedic surgeons regis tered with the Canadian Orthopaedic Association and the Canadian O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Other studies have explored the presence and effects of microaggressions, male culture, and misidentification and highlighted the lack of mentoring and harassment faced by female and URiM orthopaedic surgeons [17][18][19][20][21][22][23] . In a study by Brooks et al, 89% of surveyed Black orthopaedic surgeons experienced some form of racial microaggression in the workplace, with higher rates reported by Black female surgeons 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have explored the presence and effects of microaggressions, male culture, and misidentification and highlighted the lack of mentoring and harassment faced by female and URiM orthopaedic surgeons [17][18][19][20][21][22][23] . In a study by Brooks et al, 89% of surveyed Black orthopaedic surgeons experienced some form of racial microaggression in the workplace, with higher rates reported by Black female surgeons 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for this study was previously published as a preprint (https://osf.io/e5c6n/). The definitions of gender-based and sexual harassment used throughout the survey and the primary outcome of this survey quantifying the prevalence of gender-based and sexual harassment were previously published 1 . This study was approved by the Hamilton Integrated Research Ethics Board (Project #4848).…”
Section: Methodsmentioning
confidence: 99%
“…Survey development has been previously published in detail 1 . Briefly, we developed a unique 116-item cross-sectional survey to assess the prevalence of gender-based and sexual harassment within orthopaedic surgery and investigate details on these harassment behaviors, including who the perpetrator(s) was/were and when the behavior(s) occurred (Appendix).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual harassment is common in medicine ( 1 ) and oncology ( 3 ) yet rarely reported to persons in authority ( 8 ). A recent multispecialty study from an academic medical institution suggested that the reporting rate was only 11% in that setting ( 7 ), and the Canadian Orthopaedic Association discovered a reporting rate of only 17.5% among orthopedic surgeons ( 9 ). This study confirms that low rates of reporting also occur in oncology and suggests reliance on reporting systems alone is unlikely to suffice; preventive initiatives are essential.…”
mentioning
confidence: 99%